Writing development stories - Masterton, Murray. (2008)
Virgilio has explained what Development Journalism means and what a development journalism story is. I agree with most of this, especially when he says it adheres to the same standards of fairness, accuracy, balance and journalism ethics as conventional journalism. That means it is in essence, no different from conventional journalism, if even that can be isolated or defined. This means that writing a development journalism story should be no different from writing any worthwhile "conventional" journalism story, whether it is news or a feature. Yet to many people it is still different.